THE EFFECTIVENESS OF CALLA MODELS ON IMPROVING ENGINEERING STUDENTS’ COMMUNICATIVE COMPETENCE - Cahyaningati, Desi Tri (Educate, 2012)
Desi Tri Cahyaningati Politeknik Perkapalan Negeri Surabaya dtricahyaningati@yahoo.com Abstract This research was intended to meet the objective of the study: to examine the effectiveness of CALLA Models in improving students’ communicative competence. This study revealed several important findings. Firstly, group of students who receive CALLA Model is more effective in improving students’ communicative competence compared to control group who do not receive Strategies-Based Instruction. The statistical computation also shows that there was enough evidence to reject the null hypothesis. Based on the result of this study, there were some suggestions made by the writer which are addressed to English teacher, students and future researchers. It is hoped that English teachers could not only know how to teach the language, but also know how to develop students’ learning strategies. Thus, learners are demanded to learn and use more learning strategies. The students may try or use any learning strategies which enable them to be better in speaking English. Key Words: CALLA Models, communicative competence Abstrak Penelitian ini bertujuan untuk mengetahui efektivitas Model Calla dalam meningkatkan kompetensi komunikatif siswa. Penelitian ini mengungkapkan beberapa temuan penting. Pertama, sekelompok mahasiswa yang menerima Model Calla lebih efektif dalam meningkatkan kompetensi komunikatif siswa dibandingkan dengan kelompok kontrol yang tidak menerima Strategies-Based Instruction. Perhitungan statistik juga menunjukkan bahwa ada cukup bukti untuk menolak hipotesis nol. Berdasarkan hasil penelitian, ada beberapa saran yang ditujukan kepada guru bahasa Inggris, mahasiswa dan peneliti masa depan. Diharapkan bahwa guru bahasa Inggris tidak hanya tahu bagaimana mengajarkan bahasa, tetapi juga tahu bagaimana mengembangkan strategi belajar siswa. Dengan demikian, peserta didik dituntut untuk belajar dan menggunakan strategi belajar yang lebih baik. Para siswa dapat mencoba atau menggunakan strategi pembelajaran yang memungkinkan mereka menjadi lebih baik dalam berbicara bahasa Inggris. Kata Kunci: Model CALLA, kompetensi komunikatif